A foresight toolkit for smart specialization and entrepreneurial discovery. (June 2016) - Gheorghiu, Radu; Andreescu, Liviu; Curaj, Adrian
Highlights: Discusses increasing prevalence of smart specialization strategies for research and innovation (RIS3) in Europe. Proposes a 'toolkit' consisting of a structure for the entrepreneurial discovery process and associated instruments. Illustrates with the use of foresight in one national RIS3 and other parallel entrepreneurial discovery streams. Describes design combining data analytics and argument-based consensus instruments. Abstract: Smart specialization strategies (RIS3) have exploded in number across Europe over the past couple of years, among others due to the European Commission's sustained effort – both conceptual and at the level of policy – to push this notion forward. What lies beneath the spate of recent RIS3s, in terms of specialization options as well as of the processes through which the latter were reached, is only now beginning to be examined in depth. Notably, the Commission did not offer a proper blueprint for RIS3-making, but opted instead to suggest a wide range of possible instruments. Based on our experience with the Romanian strategy-building process, in this article we outline a foresight-based toolkit for smart specialization and entrepreneurial discovery, though we too stop short of proposing a detailed full-fledged blueprint.